ChemInform Abstract: Synthetic Applications of 2‐(Azidomethyl)allyltrimethylsilane. Issue 25 (3rd June 2013) - Ferrini, Serena; Cini, Elena; Taddei, Maurizio
Abstract The stable azide (I) is successfully applied to thermal cycloadditions with alkenes to give triazoline (III) or different types of aziridines.